Resilience in young children: A Delphi study to reach consensus on definitions, measurement and interventions to build resilience. Issue 13 (2nd October 2020) - Avdagic, Elbina; Wade, Catherine; McDonald, Myfanwy; McCormack, Derek; Dakin, Penny; Macvean, Michelle; Hayes, Laura; Phan, Tracey
ABSTRACT: In the absence of agreement about child resilience, this study used a Delphi procedure with 32 experts in child development to reach agreement about child resilience. According to participants child resilience is best defined as a process whereby a child develops the capacity to adapt when experiencing adversity, although the experience of adversity is not essential to developing resilience. Resilience is multiply determined and can be learned. Consensus was not reached regarding measurement of resilience, but participants endorsed principles to guide measurement. Multiple intervention options were endorsed, with the agreement that both child and environment be targeted. This study provides directions for improving understanding and measurement of child resilience, and will guide practice by professionals working with families to promote child resilience.